2016
DOI: 10.18632/oncotarget.12656
|View full text |Cite
|
Sign up to set email alerts
|

C5a receptor (CD88) promotes motility and invasiveness of gastric cancer by activating RhoA

Abstract: PurposeAnaphylatoxin C5a is a strong chemoattractant of the complement system that binds the C5a receptor (C5aR). The expression of C5aR is associated with poor prognosis in several cancers. However, the role of C5aR in gastric cancer (GC) is unknown. The aim of this study was to examine the role of C5aR on GC cell motility and invasion.Experimental DesignThe mechanism of invasion via C5aR was assessed by analyzing cytoskeletal rearrangement and RhoA activity after C5a treatment. Moreover, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 49 publications
(56 reference statements)
1
41
0
1
Order By: Relevance
“…Complement also promotes tumor cell motility and invasiveness through induction of metalloproteinases from tumor cells, degradation of extracellular matrix and increased expression of stress fibers and filopodia 104-106 . C3aR signaling, for instance, is implicated in the dissemination of cancer to the nervous system by disrupting the blood-cerebrospinal fluid barrier 107 .…”
Section: Role Of Complement In Cancermentioning
confidence: 99%
“…Complement also promotes tumor cell motility and invasiveness through induction of metalloproteinases from tumor cells, degradation of extracellular matrix and increased expression of stress fibers and filopodia 104-106 . C3aR signaling, for instance, is implicated in the dissemination of cancer to the nervous system by disrupting the blood-cerebrospinal fluid barrier 107 .…”
Section: Role Of Complement In Cancermentioning
confidence: 99%
“…Aberrant expression of C5aR1 has been detected in squamous cell carcinoma, adenocarcinoma and transitional cell carcinoma from various organs, and vascular invasion appears to be correlated with the expression of C5aR1 (REFS 67,92,93 ). Cell invasiveness has been shown to occur in response to C5a-induced secretion of metalloproteinases from C5aR1-expressing cancer cells and degradation of ECM 68 .…”
Section: Feeding Inflammation and Tumorigenesismentioning
confidence: 99%
“…In addition, leukaemia cell lines as well as clonogenic blasts derived from patients with chronic myeloid leukaemia or acute myeloid leukaemia show increased cell adhesion in response to C3a and C5a fragments 95 . In a model of gastric cancer, C5a promoted the invasiveness of human gastric cancer cell lines (the adenosquamous carcinoma cell line MKN1 and the tubular adenocarcinoma cell line MKN7) via conversion of RhoA-guanosine diphosphate (RhoA-GDP) to RhoA-guanosine triphosphate (RhoA-GTP), resulting in morphological cell changes and increased expression of stress fibres and filopodia 92 .…”
Section: Feeding Inflammation and Tumorigenesismentioning
confidence: 99%
“…Because C5aRs have been reported to be expressed by a range of human and murine tumor cell types (14,29,30), we next investigated receptor expression by B16.F0 melanoma cells. Quantitative PCR (qPCR) analysis showed that cultured B16.F0 cells express mRNA for C5aR1 and C5aR2, albeit at much lower levels than in J774 macrophages (Fig.…”
Section: C5ars Are Expressed By B16f0 Melanoma Cellsmentioning
confidence: 99%